The failure of externally-driven advocacy initiatives to contextualise sub-Saharan "marginalised women". Issue 2 (17th February 2021) - Bedigen, Winnie; Mdee, Anna; Temlong, Rinmicit; Thorley, Lisa; Tshomba, Patricia
ABSTRACT: This paper challenges the assumptions and practices of many externally-driven women's advocacy initiatives in sub-Saharan Africa. It examines much misunderstood concepts (advocacy, agency and empowerment) and highlights how their constructions are fundamentally flawed. It draws conclusions from advocacy training for women conducted by an international NGO in Nigeria and DRC. Illiteracy, poverty and unequal access to and control over resources all constitute barriers to advocacy. The study highlights the ineffectiveness of externally driven advocacy initiatives delivered through training events. It suggests that more nuanced and context-appropriate processes of change will more effectively identify and challenge structures of oppression.